A workshop help in Ubon (Canberra, 1995)
Contents: Role of soil organic matter in sustainable agricultural systems; the role of mulches and terrecing in crop production and water soil and nutrient management; organic matter for mutrients and organic residues for rice; soil fertility management in the rainfed lowland environment fo the Lao.
Keywords: Agricultural chemistry,Nông hóa